Virtual Exhibition Room in the Pandemic Era - Arsita Pinandita; Nofrizaldi Nofrizaldi; Uzda Nabila Shabiriani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Covid-19 pandemic has changed the various social structures in many aspects of life. All are helpless under their knees to the power of the virus spreads. Rescue activities and adapt to the situation need to be worked with an innovation. Interactive spaces for gathering, such as buying and selling, public activities, and various other public facilities are minimally done by reducing face-to-face contact. Exhibition is the one of activity that is quite important in the creative world and requires direct interaction with many people. Exhibitions that gather large numbers of people are not possible while the pandemic is still ongoing. It is not clear when the pandemic will end, but it requires new creative means in organizing exhibitions. Virtual technology is a way out to bridge new possibilities for physical reality presented by conventional exhibition room. Virtual exhibitions are expected to have the opportunity during this pandemic to maintain the creative process of art enthusiast. The virtual space in the form of an exhibition is also an important part for creators to adapt to their appreciative public.